Examining the psychological strain-affective organisational commitment relationship when jointly moderated by emotional support and in-group collectivism: a cross-cultural perspective. (30th May 2023) - Junior, David L. Ford; Fang, Ray; Ismail, Kiran M.; Ziegler, Laurie L.; Chen, Hao; McNulty, Diane
We develop a framework to study the effects of emotional support in the relationship between psychological strain and affective organisational commitment in different cultural contexts. Based on the job demands-resources model and conservation of resources theory, we hypothesise that employees' emotional support and in-group collectivism orientation jointly moderate the relationship between psychological strain and affective organisational commitment. We tested the hypothesis on a sample of 2, 702 respondents from eight different countries: Germany, India, Indonesia, Poland, South Korea, Turkey, United Arab Emirates, and the USA. The results highlight the roles of emotional support and in-group collectivism in employees' responses to psychological strain.